(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Subalternation is a fundamental postcolonial concept and refers to the social process of making someone a subaltern. The country’s top class allegedly exploits the impoverished of a country in the name of patriotism. The class of native masters maintains their authority and advantages. This research aims to examine how well-known writer and activist Arundhati Roy has portrayed members of lower castes, untouchables, tribals, and women, among many other oppressed areas of society, in a selection of her works.